Monocyte to High-Density Lipoprotein Ratio: A Novel Inflammation Marker Related to Diabetic Retinopathy - Işıl Çakır; Hasan Basri Arifoğlu; Nahide Ekici Günay; Emine Pangal; Derya Şahin; Gökçen Alıcı Sert; Necati Duru (Erciyes Medical Journal, 2020)
Objective: The most common microvascular complication of diabetes is diabetic retinopathy (DR). A new and recently emerged marker of oxidative stress and inflammation is monocyte to high-density lipoprotein cholesterol ratio (MHR). Platelet to lymphocyte ratio (PLR) and neutrophil to lymphocyte ratio (NLR) have also been shown as they are biomarkers of systemic inflammation in various diseases. The present study aims to assess MHR, its predictive value and relations between other inflammation markers in DR patients. Materials and Methods: Sixty-eight patients with DR, fifty-four DM patients without DR and forty-two control subjects were included in this study. Complete blood count, lipoprotein and uric acid levels were recorded. MHR was calculated. Results: MHR, NLR and PLR were statistically significantly higher in DR group than DM without DR group (p=0.008, p=0.042, p=0.003, respectively). Then, receiver operating characteristic (ROC) curve analysis was performed and pointed that MHR predicted DR using a cut-off level of 0.0156 with 63% sensitivity and 76% specificity. Conclusion: In this study, we investigated MHR in DR patients and its relationship with other inflammatory markers, lipoproteins and uric acid. We suggested that an elevated admission of MHR may be of benefit to detect DR and to determine the CVD risk of these patients.